Determining the Characteristics of Sodium Benzoate (E211) Production Using Mathematical Method - Kovac Kralj, Anita (Journal of Applied Solution Chemistry and Modeling, 2012)
The productivity of a particular product is highly effective if we know the chemical kinetics. Determining chemical kinetics requires a fundamental knowledge of reactants’ declining concentrations or the formation of product concentration. Concentration can be determined by double-linear extrapolation, using the conductivity measurement of strong electrolytes. This method is based on two linear sloped-lines from which the linear constants from different diagrams can be read: 1) The first diagram represents linear time dependence regarding difference in conductivity 2) The second diagram represents linear difference in conductivity dependence regarding concentration. Sodium benzoate (NaC6H5CO2) is a preservative. It is produced by the neutralization of benzoic acid (C7H6O2) with sodium hydroxide (NaOH) in a stirred batch reactor under different room temperatures: NaOHÂ + C7H6O2 <–> NaC6H5CO2 + H2O The kinetic parameters and characteristics of sodium benzoate production (activated energy, reaction rate constant, rate order) were determined.